Logistic Regression Analysis in Revealing Probability of Indonesian Moslem Community's Understanding About Cash Waqf Linked Sukuk (CWLS) - Dwi Retno Widiyanti (Perbanas Institute, 2022)
Cash Waqf Linked Sukuk (CWLS) is one of the innovative fiscal instruments through Islamic Financial Institutions in Indonesia that uses waqf funds as sukuk investment. The collection of waqf funds is still experiencing obstacles such as: lack of understanding of the Muslim community on the concept of the importance of CWLS, lack of public trust in cash waqf institutions and lack of willingness to donate cash waqf. This study conducted a survey of 151 potential Indonesian Muslim respondents consisting of civil servants, entrepreneurs, academics, and households. By using logistic regression analysis, it is expected to produce findings related to factors that affect understanding of the Muslim community regarding cash waqf linked sukuk (CWLS). Based on the results of the analysis with a significance tolerance level of 0.05%, it was concluded that formal education, income, and age had a statistically significant effect on understanding of CWLS. Based on the log of odds value, the younger respondents with the higher income and the higher formal education has more probability to have understanding on CWLS.